Aristocratic deer hunting in late Anglo-Saxon England: a reconsideration, based upon the Vita S. Dvnstani. (24th July 2017) - Flight, Tim
Abstract: Scholarship is divided over whether there existed a tradition of recreational hunting in Anglo-Saxon England, in addition to pragmatic forms of venery, and the extent to which it was altered by the Normans after the Conquest. However, hunting scholarship has hitherto neglected the detailed account of a recreational royal deer hunt in the Vita S. Dvnstani . By analysing this account, which describes a hunt resembling a typically 'Norman' chasse par force de chiens, I reassess the evidence for the nature of hunting in laws, charters, and the archaeological record. I posit that the Anglo-Saxon aristocracy hunted in a similar manner to the Normans, and that hunting was a socially inscribed pursuit, legally restricted to the ruling classes long before 1066. This argument supports the definition of the disputed charter term haga ('enclosure') in certain instances as an Anglo-Saxon hunting park. Finally, I suggest the existence of a specialized Anglo-Saxon hunting dog developed specifically to hunt large quarry in the 'Norman' manner.